RUANG BELAJAR YANG INOVATIF: MEMANFAATKAN TIKTOK UNTUK PEMBELAJARAN SISWA SEKOLAH DASAR - Alpian, Yayan; Anggraeni, Sri Wulan; Mahpudin, Mahpudin; Wahyuningsih, Sri; Asmahasanah, Salati (LPPM Univ. Ibn Khaldun Bogor, 2024)
The implementation of TikTok as an innovative learning tool for elementary school students is carried out through a community service program. The use of TikTok social media in the learning process aims to increase students' engagement, understanding, and creativity in the learning process. The program was designed using lecture and question-and-answer methods, focusing on the importance of using TikTok wisely and responsibly. The results of this program show a significant increase in student engagement, material understanding, and creativity development in educational content creation. TikTok has proven to be an effective engaging and interactive learning medium that motivates students to be more active in the learning process. Despite the challenges related to supervision in the use of social media, this program illustrates the significant potential of TikTok as an educational tool that can be adapted to meet students' learning needs in the digital era.